Die eerste dekade van Interkulturele Kommunikasie - H.J. Groenewald (Communicare)
The first decade of intercultural communication: An overview of some important books This paper deals with eleven of the more important books on intercultural communication published over the past decade. A basic point of departure is that intercultural communication has become increasingly important due to factors such as technological, economic and political developments. The books are discussed in terms of the following issues: delimitation of the field and level of analysis: participating parties and symbol systems; perception; attitudes, values and beliefs; theoretical contributions, such as dialogue and cultural criticism; intercultural research; and applications. It is concluded that reasonable agreement exists among the authors on the importance of the field, and the nature of the major variables, although they are incorporated within different theoretical frameworks. It is predicted that the present decade will see a growth in the area of research, which up to the present seems to have been lagging behind.